2022
DOI: 10.3390/nano12132257
|View full text |Cite
|
Sign up to set email alerts
|

Lead(II)-Azido Metal–Organic Coordination Polymers: Synthesis, Structure and Application in PbO Nanomaterials Preparation

Abstract: The current study aims to explain recent developments in the synthesis of Pb(II)-azido metal-organic coordination polymers. Coordination polymers are defined as hybrid materials encompassing metal-ion-based, organic linkers, vertices, and ligands, serving to link the vertices to 1D, 2D, or 3D periodic configurations. The coordination polymers have many applications and potential properties in many research fields, primarily dependent on particular host–guest interactions. Metal coordination polymers (CPs) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 135 publications
0
0
0
Order By: Relevance
“…The IR and 11 B NMR data correlate with those reported [53]. by different methods [52], it seems that the softer boron cluster is preferable to form the coordination environment of the metal atom as compared to the azido group. We concluded that the N3 group is too hard to be coordinated by lead(II) in the presence of BH groups.…”
Section: Methodssupporting
confidence: 81%
See 2 more Smart Citations
“…The IR and 11 B NMR data correlate with those reported [53]. by different methods [52], it seems that the softer boron cluster is preferable to form the coordination environment of the metal atom as compared to the azido group. We concluded that the N3 group is too hard to be coordinated by lead(II) in the presence of BH groups.…”
Section: Methodssupporting
confidence: 81%
“…The units are interconnected through CH…HB contacts (Figure 6), forming channels parallel to axis c, which are filled with disordered solvent molecules. In spite of the ability of lead(II) to form compounds with the N 3 group coordinated by different methods [52], it seems that the softer boron cluster is preferable to form the coordination environment of the metal atom as compared to the azido group. We concluded that the N 3 group is too hard to be coordinated by lead(II) in the presence of BH groups.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Metal coordination polymers (CPs) are a promising class of crystalline porous materials composed of metal-containing nodes and organic ligands. Due to their intriguing topology, easyto-functionalize surface structure, and properties in gas storage and separation, ion exchange, sensing luminescence, etc., CPs have drawn a lot of attention in recent decades [1][2][3][4][5][6][7][8][9][10][11][12]. The structure diversity of CPs and their chemical properties are almost limitless on the basis of the properties of metal ions and their coordination modes with various organic ligands.…”
Section: Introductionmentioning
confidence: 99%
“…There have been several achievements in MOF materials with high proton conductivity by systematic design modifications, such as the introduction of NH 4 + , H 3 O + , and HSO 4 − into the pores of the framework [8]. However, there have been few studies on the physical properties of MOF thin films [9][10][11], such as adjusting the film morphology and the fabrication of dense MOF films [12][13][14]. Therefore, the simple preparation of stable and high proton conductive MOF thin films remains a great challenge [15].…”
Section: Introductionmentioning
confidence: 99%